Temporal control of gene deletion in sensory ganglia using a tamoxifen-inducible Advillin-Cre-ERT2 recombinase mouse - Lau Joanne; Minett Michael S; Zhao Jing; Dennehy Ulla; Wang Fan; Wood John N; Bogdanov Yury D (SAGE Publishing, 2011)
Abstract Background Tissue-specific gene deletion has proved informative in the analysis of pain pathways. Advillin has been shown to be a pan-neuronal marker of spinal and cranial sensory ganglia. We generated BAC transgenic mice using the Advillin promoter to drive a tamoxifen-inducible CreERT2 recombinase construct in order to be able to delete genes in adult animals. We used a floxed stop ROSA26LacZ reporter mouse to examine functional Cre expression, and analysed the behaviour of mice expressing Cre recombinase. Results We used recombineering to introduce a CreERT2 cassette in place of exon 2 of the Advillin gene into a BAC clone (RPCI23-424F19) containing the 5' region of the Advillin gene. Transgenic mice were generated using pronuclear injection. The resulting AvCreERT2 transgenic mice showed a highly specific expression pattern of Cre activity after tamoxifen induction. Recombinase activity was confined to sensory neurons and no expression was found in other organs. Less than 1% of neurons showed Cre expression in the absence of tamoxifen treatment. Five-day intraperitoneal treatment with tamoxifen (2 mg per day) induced Cre recombination events in ≈90% of neurons in dorsal root and cranial ganglia. Cell counts of dorsal root ganglia (DRG) from transgenic animals with or without tamoxifen treatment showed no neuronal cell loss. Sensory neurons in culture showed ≈70% induction after 3 days treatment with tamoxifen. Behavioural tests showed no differences between wildtype, AvCreERT2 and tamoxifen-treated animals in terms of motor function, responses to light touch and noxious pressure, thermal thresholds as well as responses to inflammatory agents. Conclusions Our results suggest that the inducible pan-DRG AvCreERT2 deleter mouse strain is a useful tool for studying the role of individual genes in adult sensory neuron function. The pain phenotype of the Cre-induced animal is normal; therefore any alterations in pain processing can be unambiguously attributed to loss of the targeted gene.